Autoimmune Regulator Deficiency Results in a Decrease in STAT1 Levels in Human Monocytes - Zimmerman, Ofer; Rosen, Lindsey B.; Swamydas, Muthulekha; Ferre, Elise M. N.; Natarajan, Mukil; van de Veerdonk, Frank; Holland, Steven M.; Lionakis, Michail S. (Frontiers in Immunology, 2017)
Autoimmune polyendocrinopathy-candidiasis-ectodermal dystrophy (APECED) is a rare primary immunodeficiency disorder typically caused by biallelic AIRE mutations that manifests with chronic mucocutaneous candidiasis (CMC) and autoimmunity. Patients with STAT1 gain-of-function (GOF) mutations also develop CMC and autoimmunity; they exhibit increased STAT1 protein levels at baseline and STAT1 phosphorylation (pSTAT1) upon interferon (IFN)- stimulation relative to healthy controls. AIRE interacts functionally with a protein that directly regulates STAT1, namely protein inhibitor of activated STAT1 (PIAS1), which inhibits STAT1 activation. Given the common clinical features between patients with AIRE and STAT1 GOF mutations, we sought to determine whether APECED patients also exhibit increased levels of STAT1 protein and phosphorylation in CD14+ monocytes. We obtained peripheral blood mononuclear cells (PBMC) from 8 APECED patients and 13 healthy controls and assessed the levels of STAT1 protein and STAT1 tyrosine phosphorylation at rest and following IFN- stimulation, as well as the levels of STAT1 mRNA. The mean STAT1 protein levels in CD14+ monocytes exhibited a 20% significant decrease in APECED patients both at rest and after IFN- stimulation relative to that of healthy donors. Similarly, the mean peak value of IFN-induced pSTAT1 level was 20% significantly lower in APECED patients compared to that in healthy controls. The decrease in STAT1 and peak pSTAT1 in APECED patients was not accompanied by decreased STAT1 mRNA or anti-IFN autoantibodies; instead, it correlated with the presence of autoantibodies to type I IFN autoantibodies and decreased AIRE-/- monocyte surface expression of IFN-receptor 2. Our data show that, in contrast to patients with STAT1 GOF mutations, APECED patients show a moderate but consistent and significant decrease in total STAT1 protein levels, associated with lower peak levels of pSTAT1 molecules after IFN- stimulation.